Teaching lifespace working by using the lifespace in teaching - Fiona Feilberg (Scottish Journal of Residential Child Care)
One of the most useful, fruitful and illuminating models I have found of understanding the work of residential child care has been that of lifespace. When I was undertaking my own social work training I remember struggling, at times, to use the methods I was being taught to help me to understand and develop my work within a group environment. Often these models were based upon the assumption that working one-to-one was the norm. It was not that I was unable to amend what I was learning to make it more relevant, but that I had to struggle to make the models fit the complexity of working within a residential setting. The teaching which I received on the concept of lifespace provided me with a theoretical base which drew upon the wider range of teaching on child development and group dynamics. It also provided affirmation of the work I had undertaken, in that it confirmed the effectiveness of working within a group setting as an effective and valid option rather than as a poor substitute for individual work.